PENDIDIKAN SEKOLAH DASAR 2024; MENYIAPKAN GENERASI EMAS DENGAN KETERAMPILAN ABAD 21 - Moh Pudali Arodani; Misriyani; Fardan Firdausy; Mas odi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Primary School (SD) education in 2024 aims to prepare the young generation who are able to compete and innovate in the ever-growing digital era. The